2018
DOI: 10.1111/tbj.13123
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of the limitations of near-infrared imaging in detecting axillary sentinel lymph nodes in primary breast cancer

Abstract: We compared the performance of near-infrared imaging using indocyanine green (ICG) with the radioisotope (ISO) method to detect sentinel lymph nodes (SLNs) in breast cancer, to analyze predictive factors for negative ICG identification. The study included 122 patients who underwent sentinel lymph node biopsy (SLNB) using the combined ISO and ICG technique for primary breast cancer. We assessed the putative association between pathologic/clinical variables and ICG failure to detect SLNs. The ISO identification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 17 publications
2
18
0
1
Order By: Relevance
“…This association provides a better outcome for sentinel lymph node detection in our series than in other French studies. 22 Our results are concordant with literature. In the two largest published series of 301 and 847 patients, authors found a detection rate of 99% and 97%, respectively, a high concordance rate and a better sensitivity of indocyanine green for positive sentinel lymph node than radioisotopes alone.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This association provides a better outcome for sentinel lymph node detection in our series than in other French studies. 22 Our results are concordant with literature. In the two largest published series of 301 and 847 patients, authors found a detection rate of 99% and 97%, respectively, a high concordance rate and a better sensitivity of indocyanine green for positive sentinel lymph node than radioisotopes alone.…”
Section: Discussionsupporting
confidence: 92%
“…Infracyanine ® is a specialty of indocyanine green that does not contain iodine and thus reduces the risk of allergy. This association provides a better outcome for sentinel lymph node detection in our series than in other French studies 22 …”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Zeng et al analyzed 40 clinical studies mainly from Asia since 2010 and reported an average ICG SLN detection rate of 95% but with a higher number of lymph nodes resected (from 1.75 to 3.8). As observed in our experience, a lower detection rate for ICGSLN was observed in overweight and obese patients . In contrast to Cattin et al experience, we did not adopt for this first prospective study, a variation in the amount of ICG injected.…”
mentioning
confidence: 99%